The Erotics of Materialism : Lucretius and Early Modern Poetics - Hock, Jessie (University of Pennsylvania Press, 2021)
Cover -- The Erotics of Materialism -- Title -- Copyright -- CONTENTS -- Introduction. The Supple Snare -- Chapter 1. Materializing the Lyric Tradition: Lucretius and the Poetry of Pierre de Ronsard -- Chapter 2. Poetry in a Time of War: Lucretius and Poetic Patrimony in Pierre de Ronsard's Sonnets pour Helene and Remy Belleau's Pierres précieuses -- Chapter 3. "Like gold to aery thinness beat": John Donne's Materialisms -- Chapter 4. Lucy Hutchinson and the Erotic Reception of Lucretius -- Chapter 5. Lucretian Poetics and Women's Writing in Margaret Cavendish's Poems and Fancies -- Epilogue. This Is Our Venus -- Notes -- Bibliography -- Index -- Acknowledgments.